2011
DOI: 10.1002/gcc.20926
|View full text |Cite
|
Sign up to set email alerts
|

Copy number defects of G1‐Cell cycle genes in neuroblastoma are frequent and correlate with high expression of E2F target genes and a poor prognosis

Abstract: The tightly controlled network of cell cycle genes consists of a core of cyclin dependent kinases (CDKs) that are activated by periodically expressed cyclins. The activity of the cyclin-CDK complexes is regulated by cyclin dependent kinase inhibitors (CDKIs) and multiple signal transduction routes that converge on the cell cycle. Neuroblastoma are pediatric tumors that belong to the group of small round blue cell tumors, characterized by a fast proliferation. Here, we present high throughput analyses of cell c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 41 publications
1
52
0
Order By: Relevance
“…Neuroblastoma has a complex genetic profile that can include MYCN amplification, somatic activating mutations in the ALK oncogene, and other aberrations that activate CDK4/6 activity (6,25). It has also recently been shown that high-risk neuroblastoma may be defined by activation of telomere maintenance mechanisms caused by MYCN amplification, TERT rearrangements, or ATRX mutations (26), and relapsed neuroblastomas are frequently associated with RAS/mitogen-activated protein kinase (MAPK) pathway mutations that could also influence ribociclib sensitivity (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroblastoma has a complex genetic profile that can include MYCN amplification, somatic activating mutations in the ALK oncogene, and other aberrations that activate CDK4/6 activity (6,25). It has also recently been shown that high-risk neuroblastoma may be defined by activation of telomere maintenance mechanisms caused by MYCN amplification, TERT rearrangements, or ATRX mutations (26), and relapsed neuroblastomas are frequently associated with RAS/mitogen-activated protein kinase (MAPK) pathway mutations that could also influence ribociclib sensitivity (27).…”
Section: Discussionmentioning
confidence: 99%
“…CCND1, CDK4, and CDK6 have been shown to be highly expressed in neuroblastoma, and CCND1 and CDK6 expression were found to be uniformly high relative to other tumors (5)(6)(7). Genomic amplification of CCND1 (cyclin D1 tumors) and CDK4 and deletion of CDKN2A are correlated with poor prognosis and, notably, approximately 30% of neuroblastomas exhibit aberrations in genes which regulate the G 1 checkpoint (6). An RNAi kinome screen in neuroblastoma cell lines identified CDK4 as a potential therapeutic target (8).…”
Section: Introductionmentioning
confidence: 99%
“…Also, BIRC5 is established as an E2F target (Jiang et al 2004). In neuroblastoma, a high E2F activity is related to a bad prognosis (Molenaar et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The following probe sets were used to detect HDAC10 expression: neuroblastoma (AMC), 226672_s_at; neuroblastoma (NCI), 811025; and medulloblastoma (Heidelberg), A_23_P211673. Patient characteristics for the neuroblastoma (AMC), neuroblastoma (NCI), and medulloblastoma (Heidelberg) cohorts were previously published (31)(32)(33).…”
Section: Methodsmentioning
confidence: 99%
“…We reanalyzed publicly available expression data [Academic Medical Center (AMC) cohort; Gene Expression Omnibus (GEO) database accession no. GSE16476] from 40 advanced stage primary neuroblastomas (INSS stage 4) from patients before treatment with multimodal chemotherapy using the Web-based R2 microarray database (http://r2.amc.nl) (31) to determine HDAC1 to -11 expression levels. From all 11 classical HDACs, only HDAC10 expression significantly correlated with poor overall survival in this patient cohort (Table S1).…”
Section: Hdac10 Expression In Neuroblastomas Predicts Treatment Outcomementioning
confidence: 99%